Brain Foods for Cognitive Performance and Mental Health: A Scoping Review of Essential Nutrients - Dahal, Kabita (Journey for Sustainable Development and Peace Journal, 2026)
The recent breakthroughs in nutritional neuroscience indicate that food is a key factor in brain development, consolidation of memory, concentration ability and long-term cognitive ability. This article is a synthesis of the role played by the necessary nutrients that support brain activity and enhance mental sharpness. It follows a systematic review approach, which summarizes and reviews the available literature on nutrition science and neuroscience in order to explain how dietary ingredients can regulate cognitive functions. Empirical evidence shows that omega-3 fatty acids, B-vitamins, antioxidants, minerals, amino acids and complex carbohydrates have significant effects on neuronal structures, neurotransmitter production, and the general cerebral metabolism. These nutrients promote important cognitive functions, such as memory retention, attention and learning, and emotional control. Besides, the growing body of literature surrounding the gut-brain axis underscores the mutual interchange between dietary habits, gut microbiota, and neurophysiological processes that regulate affect and cognitive functionality. The finding of the paper highlights that nutritionally adequate dietary behaviours in combination with other lifestyle-based interventions are undoubtedly the key to maintaining cognitive performance and psychological well-being.